Association of Management Efficiency to Improve the Quality of Health Services in Primary Health Care : a Systematic Review - Nathan, Daniel Setiawan; Rostiaty, Erti (International Medical Journal Corp. Ltd, 2024)
Background: The goal of this study is to showed the association of management efficiency to improve the quality of health services in primary health care. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Several different online reference sources, like Pubmed and SagePub, were used to do this.. Result: In the PubMed database, the results of our search brought up 387 articles, whereas the results of our search on SagePub brought up 187 articles. The results of the search conducted for the last year of 2013 yielded a total 23 articles for PubMed and 11 articles for SagePub. In the end, we compiled a total of 7 papers, 5 of which came from PubMed and 2 of which came from SagePub. We included three research that met the criteria. Conclusion: The research does not explicitly show a relationship between efficiency and patient satisfaction, but it does show a relationship to facility improvement and development. Much literature shows a relationship between improvement and development of facilities on patient satisfaction.